2016
DOI: 10.18869/acadpub.ijrr.14.4.331
|View full text |Cite
|
Sign up to set email alerts
|

Indoor radon measurements in residential dwellings in Qom, Iran

Abstract: Background: Inhala on of radon and its short-lived decay products is one of the most significant sources of exposure to natural radia on. Radon is the second cause of lung cancer in the popula ons. The present study was carried out under the projects of na onal radon, with the aim of determining the concentra on of indoor in the city of Qom located in the central semi-arid region of Iran. Materials and Methods: Radon measurements were carried out in 123 dwellings using passive sampling with CR-39 detectors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…The research was performed with the aim of assessing the prevalence of SBS among primary school students in Qom, Iran, and the association between SBS symptoms and personal, psychosocial and environmental factors. [10][11][12][13] . The annual average temperature and precipitation are 18.1 0 C and 161 mm, respectively.…”
Section: Objectivementioning
confidence: 99%
“…The research was performed with the aim of assessing the prevalence of SBS among primary school students in Qom, Iran, and the association between SBS symptoms and personal, psychosocial and environmental factors. [10][11][12][13] . The annual average temperature and precipitation are 18.1 0 C and 161 mm, respectively.…”
Section: Objectivementioning
confidence: 99%
“…These radionuclides cause radiological hazard externally due to the gamma ray emission and internally due to inhalation of radon and its progeny [8]. When human exposure to natural radiation source is considered, radon and its short lived decay products in the environment are the most important contributors [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Radium mainly enters the body through the food chain Radium, being chemically similar to calcium, tends to follow it in metabolic processes and becomes concentrated in bones. The alpha particles given off by radium and radon bombard the bone marrow and destroy tissues that produce red blood cells [13][14][15]. It may cause bone cancer.…”
Section: Introductionmentioning
confidence: 99%
“…When radon surfaces in the open air, it is quickly diluted to harmless concentrations, but when it enters an enclosed space, such as a house, it can sometimes accumulate to acceptably high concentrations. So, measurements of indoor radon are very important for escaping from In the past twenty years, assessments of radon concentration in indoor air have been extensively conducted for the dwellings, offices an around the world (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) . For an example of studies of indoor radon concentration in Korea, it was found that the mean value of the radon concentrations for forty rooms in Kwanak Campus, Seoul National University, Korea was 111 Bq/m 3 (13) .…”
Section: Introductionmentioning
confidence: 99%